Forced response of rotating bladed disks: Blade Tip-Timing measurements. (15th February 2017) - Battiato, G.; Firrone, C.M.; Berruti, T.M.
Abstract: The Blade Tip-Timing is a well-known non-contact measurement technique currently employed for the identification of the dynamic behaviours of rotating bladed disks. Although the measurement system has become a typical industry equipment for bladed disks vibration surveys, the type of sensors, the positioning of the sensors around the bladed disk and the used algorithm for data post-processing are still not standard techniques, and their reliability has to be proved for different operation conditions by the comparison with other well-established measurement techniques used as reference like strain gauges. This paper aims at evaluating the accuracy of a latest generation Tip-Timing system on two dummy blisks characterized by different geometrical, structural and dynamical properties. Both disks are tested into a spin-rig where a fixed number of permanent magnets excite synchronous vibrations with respect to the rotor speed. A new positioning for the Blade Tip-Timing optical sensors is tested in the case of a shrouded bladed disk. Due to the presence of shrouds, the sensors cannot be positioned at the outer radius of the disk pointing radially toward the rotation axis as in the most common applications, since the displacements at the tips are very small and cannot be detected. For this reason a particular placement of optical laser sensors is studied in order to point at the leading and trailing edges' locations where the blades experience the largest vibration amplitudes with the aim of not interfering with the flow path. Besides the typical Blade Tip-Timing application aimed at identifying the dynamical properties of each blade, an original method is here proposed to identify the operative deflection shape of a bladed disk through the experimental determination of the nodal diameters. The method is applicable when a small mistuning pattern perturbs the ideal cyclic symmetry of the bladed disk. Abstract : Highlights: The new beam shutter configuration for optical laser sensors is tested on two disks. The Blade Tip-Timing technique is verified by the strain gauge measurements. A new method to identify the operative deflection shape of the disk is proposed. The travelling operative deformed shape is identified when small mistuning occurs.